Quality of life in patients with fibromyalgia: Contributions of disease symptoms, lifestyle and multi-medication - Fernandez-Feijoo, Fátima; Samartin-Veiga, Noelia; Carrillo-de-la-Peña, María Teresa (Frontiers in Psychology, 2022)
Fibromyalgia (FM) is a disease characterized by the presence of chronic and widespread musculoskeletal pain, which causes a high negative impact on the quality of life (QoL). Although there are many studies about the QoL of patients with FM, it is unknown which variables have a main influence on it. Therefore, in the present study, we aimed to determine which FM symptoms predict a worse QoL and also to establish whether lifestyle and multi-medication are associated to QoL. We assessed a sample of 134 women with FM using a semi-structured clinical interview to explore lifestyle (diet, exercise, smoking) and medication use, and questionnaires to cover the main symptoms of this disease and QoL (SF-36). We found that the patients with FM had a poor QoL, being “physical pain” and “vitality” the most affected domains. A linear regression analysis showed that depression and anxiety assessed by HADS were the FM symptom which most significantly predicted QoL, explaining 49% of the variance. Concerning lifestyle/medication influences, we found that multiple drug treatment and smoking also predicted a worse QoL (14%). Moreover, patients who practiced exercise regularly showed better quality of life than patients who did not (regardless of the severity of FM). Thus, our results suggest that treatment strategies to improve QoL in FM should be focused on improving psychological distress, promoting regular exercise and reducing smoking and multi-medication. The data highlights the role of positive self-management practices to improve QoL in FM.